(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2024)
Introduction. In the conditions of the rapid development of e-commerce in the B2C market, it is important to ensure the effective use of marketing budgets to achieve competitive advantages. Evaluating the effectiveness of marketing spend allows businesses to optimize resources, increase return on investment, and reach a larger target audience. This requires the formation of methodological approaches for evaluating and improving the effectiveness of marketing budgets in this area. The purpose of the article. The purpose of the study is to study approaches to evaluating the effectiveness of marketing budgets in the B2C e-commerce market in order to determine the principles of increasing the effectiveness of their use. Methods. The research methodology includes a comprehensive approach combining quantitative and qualitative methods of analysis. In particular, for the in-depth study of specific examples of successful marketing strategies, such methods as economic modeling, the method of analysis and synthesis, and comparison were used. Results. The article examines approaches to evaluating the effectiveness of marketing costs in the B2C e-commerce sector, focusing on different channels, strategies and the corresponding profitability of marketing costs. The current market trends of the functioning of e-commerce platforms were analyzed and the main factors affecting the effectiveness of the use of marketing budgets of business entities were identified. The trends of the global growth of digital commerce volumes in the context of B2C sales and its functional specificity are clarified. It was determined that personalization, segmentation of customers and integration of multi-channel strategies significantly increase the efficiency of using marketing budgets. The principles of optimization of marketing costs based on the implementation of automated systems for data analysis and forecasting of consumer behavior were studied. The influence of the latest technologies, such as artificial intelligence and machine learning, on the effectiveness of using marketing budgets is considered. Conclusions. It has been proven that a reliable assessment of the effectiveness of marketing budgets in the B2C market determines a number of key aspects that ensure the maximum return on marketing investments of a business entity. At the same time, the concept of effectiveness of marketing budgets consists in a targeted approach implemented on the basis of personalization, segmentation and multi-channel integration.